Salvage autologous transplant and lenalidomide maintenance vs. lenalidomide/dexamethasone for relapsed multiple myeloma: the randomized GMMG phase III trial ReLApsE - Goldschmidt, Hartmut; Bärtsch, Marc-Andrea; Schlenzka, Jana; Becker, Natalia; Habermehl, Christina; Hielscher, Thomas; Raab, Marc-Steffen; Hillengaß, Jens; Sauer, Sandra; Müller-Tidow, Carsten; Luntz, Steffen P.; Jauch, Anna; et al. (Leukemia, 2020)
The role of salvage high-dose chemotherapy and autologous stem cell transplantation (sHDCT/ASCT) for relapsed and/or refractory multiple myeloma (RRMM) in the era of continuous novel agent treatment has not been defined. This randomized, open-label, phase III, multicenter trial randomized patients with 1st-3rd relapse of multiple myeloma (MM) to a transplant arm (n = 139) consisting of 3 Rd (lenalidomide 25 mg, day 1-21; dexamethasone 40 mg, day 1, 8, 15, and 22; 4-week cycles) reinduction cycles, sHDCT (melphalan 200 mg/m2), ASCT, and lenalidomide maintenance (10 mg/day) or to a control arm (n = 138) of continuous Rd. Median PFS was 20.7 months in the transplant and 18.8 months in the control arm (HR 0.87; 95% CI 0.65-1.16; p = 0.34). Median OS was not reached in the transplant and 62.7 months in the control arm (HR 0.81; 95% CI 0.52-1.28; p = 0.37). Forty-one patients (29%) did not receive the assigned sHDCT/ASCT mainly due to early disease progression, adverse events, and withdrawal of consent. Multivariate landmark analyses from the time of sHDCT showed superior PFS and OS (p = 0.0087/0.0057) in patients who received sHDCT/ASCT. Incorporation of sHDCT/ASCT into relapse treatment with Rd was feasible in 71% of patients and did not significantly prolong PFS and OS on ITT analysis while patients who received sHDCT/ASCT may have benefitted.